Maternal effects shape dynamic trajectories of reproductive allocation in the ladybird Coleomegilla maculata - Vargas, G.; Michaud, J. P.; Nechols, James R. (My University, 2012)
We followed lifetime trajectories of reproductive allocation in Coleomegilla maculata females of three different size classes produced by rearing beetles on three different daily larval feeding regimes (30 min, 6h or ad libitum access to eggs of Ephestia kuehniella). We hypothesized that small females would produce fewer and smaller eggs than larger females and that reproductive effort would decline with female age. Females were mated with a male from the same treatment and then isolated with ad libitum food for their entire adult lives. Egg size increased over time in all treatments; small females started off laying the smallest eggs, but increased egg size more rapidly than larger females, until all treatments converged on a similar egg size around the 20th day of oviposition. Large females realized a larger proportion of their fecundity early in life, but smaller females increased daily fecundity over time. Reproductive effort (egg mass/body mass) did not decline over 30 oviposition days; it remained constant in large females, but increased among small and medium females, suggesting gradual compensation for larval food deprivation. An increase in egg size with maternal age may be an adaptive strategy to maximize fitness on ephemeral patches of aphid prey, assuming females reproduce in a single aphid outbreak and that offspring produced later in the aphid cycle experience greater competition and risk of mortality compared to those produced earlier. We demonstrate for the first time in Coleoptera that dynamic changes in both egg size and number occur as a function of female age and illustrate that such changes are constrained by larval feeding histories via their effects on maternal body size.
Keywords: Aphidophagy; Body size; Egg size; Fecundity; Reproductive effort